Psychological distress among healthcare providers in oncology during the COVID-19 pandemic in Japan: The mediating role of moral distress and resilience - Okamura, Masako; Fujimori, Maiko; Goto, Shinichi; Ohisa, Keiko; Boku, Narikazu; Nakahara, Rika; Uchitomi, Yosuke; Suzuki, Tatsuya; Matsuda, Tomohiro (Frontiers in Psychology, 2023)
Objective: Even though vaccines have become widespread, there is an explosion of infection due to the emergence of new mutant strains, and support for healthcare providers’ mental health is necessary. The aims of this study were to explore factors associated with the psychological distress, and to determine the degree of association between moral distress, resilience and psychological distress in order to consider intervention models for psychological distress of healthcare providers involved with cancer patients during the COVID-19 pandemic. Method: We conducted a cross-sectional survey among healthcare providers at the National Cancer Center, Japan. Psychological distress was assessed by the Hospital Anxiety and Depression Scale. We also assessed moral distress using the Moral Distress Thermometer and resilience using the Connor-Davidson Resilience Scale 10 in April and May 2020 which was the first surge of the epidemic period. Results: Five hundred sixty-six of 3,900 healthcare providers (14.5%) responded. Sixty-eight percent (385/566) responders were above the Hospital Anxiety and Depression Scale cutoff. Hierarchical regression analyses indicated that nurses, allied health professionals and office workers/engineers (odds ratio = 4.63; 95% confidence interval 1.90-11.29; p < 0.001, odds ratio = 3.88; 95% confidence interval 1.88-8.00; p < 0.001, odds ratio = 2.10; 95% confidence interval 1.06-4.18; p < 0.05) as well as healthcare providers with low resilience (odds ratio = 0.88; 95% confidence interval 0.85-0.91; p < 0.001) were at risk of psychological distress. Moral distress was not significantly associated with prevalence of psychological distress. Conclusion: During the first surge of the pandemic, a high prevalence of psychological distress was demonstrated among cancer center healthcare providers. The study suggests that mental health care should be available to cancer care providers. Since the COVID-19 pandemic is still going on, in addition to the efforts by our facilities, we should consider interventions that promote resilience and a feasibility study of these interventions.